Risk Factors Affecting the Length of Improvement of Nutritional Status in Children with Congenital Heart Disease and Malnutrition - Athiyatul Aufie; Sukman Tulus Putra; Mulya Rahma Karyanti; Yoga Devaera (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: To date, limited data are available regarding the factors that contribute to the delay of improvement in nutritional status as well as data regarding the optimal duration to improve malnutrition among children with congenital heart disease (CHD). Such data are important for pediatricians to fully optimize the nutritional status for those children prior to surgical procedure This study aims to identify those aforementioned factors in hope for better surgical outcome and quality of life of children with CHD. Methods: This is a descriptive analytic study using retrospective cohort design to identify the factors that contribute to the delay of improvement in nutritional status among children with CHD. Variables such as the type of CHD, classification of CHD complexity, pulmonary hypertension, heart failure, corrective surgery, the route of nutrition access, pneumonia, diarrhea, special diets and patients undergoing routine control at the nutrition outpatient clinic were evaluated in this study. Results: A total of 216 children with a diagnosis of CHD and weight-for-length z-score under -1 SD were included in this study. Based on multivariate analysis, there were two significant risk factors, which were the occurrence of diarrhea and consulting at nutrition outpatient clinic. The improvement in nutritional status in children with CHD who did not have diarrhea was faster than those with diarrhea (HR 1.94; 95% CI 1.10 – 3.47) (p value <0.025). Improvement in nutritional status of those children that underwent control at the nutrition outpatient clinic was faster than those who did not (HR 1.87; 95% CI 1.20 – 2.92) (p value <0.006). Conclusion: Risk factors that significantly lengthen the duration of improvement in the nutritional status of CHD patients were the incidence of diarrhea and those who did not undergo control at the nutrition outpatient clinic.